Perlakuan Invigorasi untuk Meningkatkan Mutu Fisiologis dan Kesehatan Benih Padi Hibrida Intani-2 Selama Penyimpanan - ,, Purnawati; Ilyas, Satriyas; ,, Sudarsono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACT Storage condition and pathogen infection of seed can cause seed deteriorates faster. The rate of deterioration during storage could be slowed by seed invigoration, and pathogen infection could be elimited by application of natural pesticide. The objective of this research was to determine the effect of seed invigoration on seed physiological quality and health of Intani-2 hybrid rice seed during storage. All research activities were done at Laboratory of Quality Control and Plant Protection, PT. BISI International, Kediri, East Java. Split plot design was used in this experiment with 4 replications. Three seed lots of Intani-2 rice seed were used as main plot and 5 invigoration treatments were used as sub plot. Seed lot 1, 2 and 3 were harvested on 30 June 2012, 29 September 2012, and 2 November 2012, respectively. Invigoration treatments consisted of untreated, priming with ascorbic acid 40 ppm, osmoconditioning with KNO3 2%, osmoconditioning with PEG -0.2 MPa, and hydropriming. All invigoration treatments were added with clove oil 0.3%. Osmoconditioning with KNO3 2% + clove oil 0.3% was effective to maintain vigour index of seed lots 2 and 3 for up to 3 months storage. All seed invigoration treatments increased speed of germination before storage. Priming with ascorbic acid 40 ppm + clove oil 0.3% and osmoconditioning with PEG -0.2 MPa + clove oil 0.3% were effective to reduce the growth of Xanthomonas sp. on rice seeds monitored at 0, 2, and 3 months after storage.Keywords: ascorbic acid, clove oil, KNO3, osmoconditioning, PEG